Influence of health institution related factors on health seeking behaviors among men suffering from lower urinary tract symptoms attending surgical outpatient clinic at a county referral hospital Meru Kenya - Muriuki, Festus M.; Mbithi, Bernard W.; Oluchina, Sherry (International Journal Of Community Medicine And Public Health, 2023)
Background: Currently there is an increase in cases of men presenting with lower urinary tract symptoms (LUTS) especially in low resource countries. The purpose of this study was to establish the influence of health institution related factors on health seeking behaviors among men suffering from LUTS attending surgical outpatient clinic at Meru county referral hospital, Kenya. Methods: Descriptive cross-sectional study design was used. Population involved 120 men suffering from LUTS, 2 physicians and 2 nurses. The study tools used were questionnaires, key informant interview guides and focus group discussion guides. The quantitative data was analyzed using chi-square test and binary logistic regression. Hypothesis testing was done at an alpha level of significance of 0.05 such that any p-values below the alpha were deemed significant. Qualitative data was analyzed thematically Results: Health institutional related factors which included adequate personnel 2.57 [95% CI=1.09-6.06, p=0.032], adequate drugs 3.14 [95% CI=1.36-7.23, p=0.007], treated well by the health care workers 2.95 [95% CI=1.18-7.36, p=0.021], short duration time taken to be served in the hospital 2.40 [95% CI=1.12-5.16, p=0.025] and distance to the health facility 2.21 [95% CI=1.01-4.84, p=0.047], significant parameters associated with health seeking behaviors Conclusions: There was significance influence of health institution related factors on health seeking behaviors among men suffering from LUTS.